Effects of salt water on the ballistic protective performance of bullet-resistant body armour. (September 2019) - Dodd, S; Malbon, C; Critchley, R; Lankester, C; O'Rourke, S; Corke, T; Carr, DJ
Bullet-resistant body armour is used by law enforcement agencies and military personnel worldwide, often in inclement weather. Some fibre types used in body armour perform poorly when wet, resulting in a reduced level of protection; this is why most body armour protective elements are water-repellent treated and/or protected by a water-resistant cover. Some of the users operate in the maritime environment. The effect of salt water on body armour performance has not been previously reported. In this work the effect of soaking body armour in salt water and exposing body armour for up to 10 soaking and drying cycles in salt water was investigated. The effectiveness of the water-resistant cover was investigated by considering three cover conditions: (i) intact, (ii) cut and (iii) removed. Wet armour was heavier and provided significantly less protection from 9 mm Luger FMJ ammunition when compared to not-exposed armour irrespective of cover condition. A degradation in performance of armours exposed to soaking and drying cycles was noted, but this was similar across all regimes considered (one, three, five and ten cycles) and not as great as for wet armours.